2020
DOI: 10.2174/1871527319666200812224457
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection of Rotenone-Induced Parkinsonism by Ursolic Acid in PD Mouse Model

Abstract: Background: Parkinson’s disease (PD) is characterized by both motor and non-motor symptoms. The presynaptic neuronal protein, α-Synuclein, plays a pivotal role in PD pathogenesis and is associated with both genetic and sporadic origin of the disease. Ursolic Acid (UA) is a well-known bioactive compound found in various medicinal plants, widely studied for its anti-inflammatory and antioxidant activities. Objective: In this research article, the neuroprotective potential of UA has been further explored in Rot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 88 publications
0
45
0
Order By: Relevance
“…Various studies reported that non motor symptoms generally develop at the initial stage of PD progression so that it is not able to differentiate PD patients from others. Zahra et al (2020) reported the characteristic motor impairment in ROT-intoxicated Parkinsonian mice [31]. To check the behavioral de cit in mice, we performed various behavioral tests such as catalepsy, rotarod, pole, and footprint, which highlighted severe motor abnormalities in ROT-intoxicated PD mouse model [42][43][44][45] (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies reported that non motor symptoms generally develop at the initial stage of PD progression so that it is not able to differentiate PD patients from others. Zahra et al (2020) reported the characteristic motor impairment in ROT-intoxicated Parkinsonian mice [31]. To check the behavioral de cit in mice, we performed various behavioral tests such as catalepsy, rotarod, pole, and footprint, which highlighted severe motor abnormalities in ROT-intoxicated PD mouse model [42][43][44][45] (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…per day) orallyadministered for 7 days, then concurrent administration of Tc (21 days) and ROT-intoxication (35 days) were done similar to that Rotenone group (n = 8/group). In accordance with our previous study, dosing was administered with minor changes [19,31]. Upon completion of the dosing, behavioral analysis was carried out, and the mice were sacri ced to isolate the brains for the proteome analysis.…”
Section: Animal Dosingmentioning
confidence: 99%
“…Various studies reported that non motor symptoms generally develop at the initial stage of PD progression so that it is not able to differentiate PD patients from others. Zahra et al (2020) reported the characteristic motor impairment in ROT-intoxicated Parkinsonian mice [31]. To check the behavioral de cit in mice, we performed various behavioral tests such as catalepsy, rotarod, pole, and footprint, which highlighted severe motor abnormalities in ROT-intoxicated PD mouse model [42][43][44][45] (Fig 1).…”
Section: Discussionmentioning
confidence: 99%
“…Parkinson's disease (PD) is the most frequent and debilitating group of motor disorders in the elderly population [1,2] and has affected millions around the world from 1990 to 2015 [3]. The neuropathological features of PD are the loss of dopaminergic neurons in vulnerable brain regions, especially in the substantia nigra (SN) [4,5].…”
Section: Introductionmentioning
confidence: 99%